Traduzioni di libri per il popolo in sloveno - Žigon, Tanja (Acta Histriae, 2020)
The article focuses on the translation of the moral tale about Genevieve of Brabant, translated into German by the Capuchin friar Martin von Cochem (1630-1712) and into Slovene by the unschooled folk poet Pavel Knobl (1765-1830) most probably in 1800. The paper first presents the historical background, along with the period in which the work was written, the content of the legend and its reception in the German territory. Particular emphasis is placed on the analysis of the first Slovenian translation, published by Ignac Kremžar in Kranj, in order to verify the reliability of the attribution of the translation to Knobl and the extent to which the translator followed the German text.
Keywords: folk books; Genevieve of Brabant; Genovefa Brabantska; Ignacij Kremžar; intercultural relations; ljudska knjiga; medkulturni stiki; Pavel Knobl; prevod; translation